THE PSYCHOMETRICS OF THE SUBJECTIVE HAPPINESS SCALE AMONG BLACKS AND WHITES - McCaskill, G. (Innov Aging, 2017)
Subjective well-being is difficult to measure. Most subjective well-being instruments have been developed and assessed on mostly White middle age adults, which suggests a need for a valid and reliable subjective well-being instrument for non-Whites. The objectives of this study were to examine the psychometric properties of the Subjective Happiness Scale (SHS) in a sample of Black and White community-dwelling adults in Alabama (N = 604) and to assess the scale’s construct validity across both racial groups. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed using the 4-item SHS. Additionally, we evaluated the internal consistency reliability for the overall sample and separately by race. The initial EFA models analyzed the factor structure for the overall sample and for each racial group separately. EFA results support a one-factor structure for the SHS for the overall sample and for each racial group separately. CFA models determined the goodness of fit of the scale for each racial group separately. The four-item scale demonstrated a significantly good fit among Blacks (χ2 = 0.11; p < 0.9; RMSEA= 0.0; CFI= 1.0; TLI= 1.0), but not Whites (χ2 = 17.8, p-value = 0.001; RMSEA= 0.15; CFI= 0.98; TLI= 0.95). The four-item scale also demonstrated adequate internal consistency for the overall sample (α = 0.89) and separately for Blacks (α = 0.89) and Whites (α = 0.89). Findings indicate that the SHS is appropriate for measuring subjective well-being among Blacks. Additional work to improve the scale’s psychometrics across both racial groups is currently underway.